Cenozoic Evolution of TRopical-Equatorial MAmmals (TREMA)–an Introduction to the Symposium Proceedings Volume - Antoine, Pierre Olivier (2017)
This special issue of the Journal of Mammalian Evolution coincides with the proceedings from a symposium held in conjunction with the 4th International Palaeontological Congress (IPC4, Mendoza, Argentina; September 28, 2014), entitled “Cenozoic evolution of TRopical-Equatorial MAmmals,” and abbreviated as TREMA. In this short introduction to the symposium proceedings, in which we present the contents of the current issue, we discuss the pivotal role of the mammalian fossil record at low latitudes for understanding the origin, structural organization, and dynamics of present mammalian biodiversity.